Mechanisms to accelerate th implementation of the Sustainable Development Goals in the Caribbean - McKenzie, Sidonia (UN ECLAC SantiagoCL, 2018)
Shows that Member States that have formailsed an institutional arrangement for SDG implementation have recorded appreciable progress in mainstreaming the SDGs and in building national ownership of the global agenda.